FOREIGN DIRECT INVESTMENT IN UZBEKISTAN: ISSUES AND PROSPECTS FOR ATTRACTION - Jumaniyazov I. T.; Aminova N. U. (Ecominds Press, 2025)
This article analyzes the recent dynamics of foreign direct investment (FDI) in Uzbekistan, highlighting both the challenges and opportunities associated with attracting international capital. Drawing on data from the World Bank, UNCTAD, and official government sources, it examines FDI trends from 2021 to 2024 and compares Uzbekistan’s performance with regional peers such as Kazakhstan and Azerbaijan. The study reveals that while FDI inflows to Uzbekistan remained relatively stable in previous years, a significant surge occurred in 2024. Key sectors attracting investment include renewable energy, manufacturing, and infrastructure. However, persistent issues such as weak contract enforcement, regulatory complexity, limited financial markets, and infrastructure bottlenecks continue to hinder investment growth. The article concludes with targeted policy recommendations aimed at improving the investment climate through legal reform, economic diversification, infrastructure development, and enhanced transparency. These measures are essential for ensuring sustained FDI inflows and fostering long-term economic development in Uzbekistan.
Keywords: Uzbekistan; Foreign Direct Investment (FDI); Investment Climate; Economic Reform; Legal Framework; Special Economic Zones (SEZs); Infrastructure; Central Asia; Comparative Analysis; Policy Recommendations.